Prototype of Room Temperature and Humidity Monitoring Device in Shallot Storage Using Microcontroller Arduino - Syaiful Nugraha; Agus Prayitno; Nilfred Patawaran; Rachmat (LPPM Politeknik Aceh Selatan, 2023)
Allium ascalonicum L or commonly referred to as shallot is one type of horticultural plant that is important because it is widely used by humans as a mixture of spices in cooking. The need for shallots increasing every day accompanied by a large number of agricultural products, causing the stability of shallot availability in Merauke County to become unstable, To support the needs of consumers shallots imported from outside Merauke. Therefore the condition of the shallots in the storage area is cold and humid. While waiting to be sold in the storage area, it must be maintained temperature and humidity to reduce decay and shrinkage. This prototype monitoring device works to measure and maintain the temperature and humidity in the storage. The data collection method in this study is Literature Study, Observation, Interview, and Documentation. Microcontroller devices are designed or made to be able to control the state of temperature and humidity in the room where the onion is stored. The device also gives notifications via text message to users to be able to find out the state of the onion storage. The results of the study conducted using the DHT11 sensor obtained a temperature measurement accuracy rate of 93.848% and a humidity accuracy rate was 91.808%. This device can detect the temperature and humidity values in the shallot storage room.